Effect of Freeze-Drying on the Sensory, Physicochemical, and Microbiological Characteristics of a Dadih-Based Functional Beverage - Nur Ahmad Habibi; Sri Darningsih; Zulkifli Zulkifli; Edmon Edmon; Citra Tristi Utami; Heri Heri; Gusnedi Gusnedi (Journal of Health and Nutrition Research, 2026)
Dadih, a traditional fermented buffalo milk product from West Sumatra, Indonesia, is widely recognized for its probiotic properties and functional health benefits. This study aimed to evaluate the effect of freeze-drying on the physicochemical, physical, sensory, and microbiological characteristics of dadih. An experimental design was employed by comparing fresh dadih with freeze-dried dadih powder, in which samples were pre-frozen at −20°C prior to drying. Physicochemical properties were analyzed through proximate composition and water activity, while physical characteristics were assessed using color parameters (L*, a*, b*) measured by a chromameter. Sensory attributes were evaluated using descriptive analysis by ten trained panelists, and microbiological quality was determined based on total lactic acid bacteria (LAB). The results showed that freeze-drying significantly reduced moisture content (from 80.56% to 2.57%) and water activity (from 0.92 to 0.21), indicating enhanced product stability and extended shelf life. The relative concentrations of macronutrients increased due to water removal. No significant changes were observed in color parameters, suggesting that visual quality was preserved. Sensory evaluation revealed a slight increase in sourness and a minor decrease in milk and fermentation aroma. The total LAB decreased from 1.0 × 10⁸ CFU/g to 7.5 × 10⁵ CFU/g after freeze-drying, representing approximately a 3-log reduction. This final count is slightly below the commonly recommended minimum level (10⁶–10⁷ CFU/g) required for probiotic efficacy, indicating a partial loss of functional viability. In conclusion, freeze-drying effectively improves the stability of dadih by significantly reducing moisture and water activity while preserving color and sensory characteristics. Unlike conventional thermal drying methods, this technique maintains product quality and concentrates nutrients, although some reduction in viable LAB occurs.